Pola Komunikasi Interpersonal Pengasuh Dan Pengurus Terhadap Santri Pondok Modern Nurul Hidayah Di Desa Bantan Tua Kecamatan Bantan Kabupaten Bengkalis - Juheri "; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Pesantren where education is capable of contributing to the birth of Muslim intellectuals , traditional function as an educational institution, a place of learning the teachings of Islam which implements the importance of religious morals. But now people have various perceptions of pesantren, ranging from old-fashioned place, a prison, a nest of terrorists, out of date until the behavior of students who graduate from pesantren have started to no longer reflect the behavior according to teachings derived. Interpersonal communication is a dialogue conducted between individuals or groups with specific goals and ways to get the desired results. This study aims to determine how the pattern of interpersonal communication pengasuh and pengurus against santri Pondok Modern Nurul Hidayah, interpersonal communication effectiveness factor, as well as communication symbols used in the interaction. This research uses descriptive qualitative research method with symbolic interaction approach. Informants in this research are pengasuh, pengurus and santri Pondok Modern Nurul Hidayah using purposive sampling. Technique.data collection techniques using participant observation, interviews and documentation. The results showed that the pattern of interpersonal communication pengasuh and pengurus against santri based on the theory of symbolic interaction that occurs symbols statements verbally and nonverbally that consists of several kinds of patterns: linear communication pattern, without any feedback from the communicant; interactional patterns that communicators and communications communicant be a mutual exchange of functions in living their functions; transactional patterns of communication that allows all interact between each other. Factor is the effectiveness of interpersonal communication: communication skills, empathy, openness, interpersonal perceptions, beliefs. Symbols used in the interaction, namely the use of verbal symbols that include spoken language and written text in the form of slogans, symbols nonverbal messages include facial, gestural, postural, paralinguistic, and artifactual, the friendly attitude that blends with gentle verbal symbols, and symbols in the form of nonverbal bell or Jaros that is used to manage all the activities of santri Pondok Modern Nurul Hidayah. Keywords : Pondok Modern Nurul Hidayah, Interpersonal Communication, Linear Communication Pattern, Interactional Communication Pattern, Transactional Communication Pattern